Effects of partial substitution of chemical fertilizer with organic manure on the activity of enzyme and soil bacterial communities in the mountain red soil - Lu, Zerang; Zhou, Yun; Li, Yongmei; Li, Chunpei; Lu, Mei; Sun, Xuemei; Luo, Zhizhang; Zhao, Jixia; Fan, Maopan (Frontiers in Microbiology, 2023)
The partial substitution of chemical fertilizer with organic manure takes on a critical significance to enhancing soil quality and boosting sustainable agricultural development. However, rare research has studied the effects of partial substitution of chemical fertilizer with organic manure on soil bacterial community diversity and enzyme activity in maize field in the mountain red soil region of Yunnan. In this study, four treatments were set up in which chemical fertilizer was substituted by 10% (M10), 20% (M20), 30% (M30) and 40% (M40) of organic manure with equal nitrogen, as well as two control treatments of single application of chemical fertilizer (M0) and no fertilization (CK). The maize (Zea mays L.) crop was sown as a test crop in May 2018. The effects of partial substitution of chemical fertilizer with organic manure on soil physicochemical properties, soil bacterial community diversity and enzyme activity were studied. The activities of Cellulase (CBH), Invertase (INV) and β-glucosidase (BG) increased with the increase of organic manure substitution ratio. The activities of β-1,4-N-acetylglucosaminidase (NAG), Urease (URE), and leucine aminopeptidase (LAP) also had the same trend. Compared with CK and M0 treatments, Shannon index increased notably by 82.91%-116.74% and 92.42%-128.01%, respectively, at the organic manure substitution ratio ranging from 10% to 40%. Chao1 and ACE index increased significantly at the organic manure substitution ratio ranging from 10% to 30%. Proteobacteria was the dominant phylum in all treatments, the relative abundance of Proteobacteria decreased as the organic manure substitution ratio increased. Redundancy analysis showed that microbial biomass C was the main factor affecting the bacterial community composition under partial replacement of chemical fertilizer treatment, while Actinobacteria was the main factor affecting the enzyme activity. In addition, the maize yield of M30 and M40 treatments was significantly higher than that of CK and M0-M20 treatments. Therefore, the partial substitution of chemical fertilizer with organic manure can improve soil biological characteristics, while increasing bacterial community diversity and soil enzyme activity. Therefore, a thirty percent organic manure substitution was determined as the optimal substitution ratio for maize farmland in the mountain red soil area of Yunnan, China.